Analisis Pendapatan dalam Menentukan Kelayakan Usaha Pifang (Bipang) di Desa Enrekeng Kabupaten Soppeng - Rifka Pratiwi; Mustari Mustari; Muh. Ihsan Said; Muhammad Dinar; Muhammad Hasan (Indonesian Journal of Social and Educational Studies, 2020)
This study aims to determine the amount of income and how profitable (feasible) Pifang (Bipang) business in Enrekeng Village is Soppeng Regency to be a business. The population in this study were 2 Pifang (Bipang) entrepreneurs in Enrekeng Village, Soppeng Regency. The data collection techniques used are interview, observation, and documentation, while the data analysis used is income analysis. The results show that the income of Pifang (Bipang) entrepreneurs in Enrekeng Village, Soppeng Regency is profitable and worth the effort. This is indicated by the significant value generated based on the analysis of R / C obtained results of 1.2, where a = R / C> 1 (each cost incurred in the amount of Rp. 1 generates revenue of 1.2 which means the Pifang businessman (Bipang) gets profits from the business that he does.